Surgical reconstruction technique of medial rectus muscle after endoscopic sinus surgery iatrogenic rupture – report of three cases - Érica Batista Fontes; Alexandre Wady Debes Felippu; André Wady Debes Felippu; Bruno Belchior de Oliveira; Dimas da Silva Rico Junior; Filippo Cascio; Mauro Goldchmit; Alexandre Felippu (Rhinology Online, 2020)
Background: Medial rectus muscle (MRM) injury is an uncommon complication of endoscopic sinus surgery (ESS). The main objective of this study is to report a systematized surgical technique in the reconstruction of the MRM after EES injury. Case presentation: The present study consists of a retrospective review of three cases of MRM injuries after ESS based on intraoperative observation with clinical and radiologic follow up. Three patients presented with total rupture of MRM after ESS and were surgically treated. To treat the lesion a multidisciplinary team composed by an ENT surgeon and an ophthalmologist used a combined approach that consisted of external and endonasal accesses. Results: All three patients presented with clinical and radiological satisfactory outcomes in their follow-ups with the resolution of the diplopia and strabismus. Discussion: In this series of cases, all ruptured MRMs were successfully retrieved by combined approaches. Early intervention, and identification of both stumps allowed a muscle-to-muscle anastomosis. The technique described provided a satisfactory aesthetic result. Conclusion: Although the present study consists of a small sample supply, we describe a feasible surgical technique in the reconstruction of an MRM total rupture after ESS.